A Noble‐Metal‐Free Porous Coordination Framework with Exceptional Sensing Efficiency for Oxygen1. Issue 50 (16th October 2013) - Lin, Rui‐Biao; Li, Fang; Liu, Si‐Yang; Qi, Xiao‐Lin; Zhang, Jie‐Peng; Chen, Xiao‐Ming
<x xml:space="preserve">Abstract</x> Light material: By virtue of the unique framework structure and very high oxygen permeability, a noble‐metal‐free, highly fluorescent, porous coordination polymer demonstrates a rapid, reversible, efficient, stable, and selective fluorescence‐quenching response toward oxygen.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>